7‐chloroquinoline‐chalcone/‐pyrazoline conjugates: Synthesis, antimycobacterial and cytotoxic activities. (5th April 2022) - Kumar, Sumit; Saini, Anu; Kumar, Ankush; Raj, Raghu; Kumar, Vipan
Abstract: A series of 1 H ‐1, 2, 3‐triazole linked 7‐chloroquinoline‐chalcones and 7‐chloroquinoline‐pyrazolines were synthesized using 1, 3‐dipolar cycloaddition and evaluated for their antimycobacterial and cytotoxic activities. The compound having O ‐methoxy substituent on ring A and p ‐methoxy on ring B along with pyrazoline ring exhibited moderate activity and was noncytotoxic. Abstract : Synthesis, antimycobacterial, and cytotoxic evaluation of quinoline‐chalcone/ N ‐acetylpyrazoline conjugates against mc 2 6230 strain.